(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
The objective of the present study was to evaluate the diagnostic performance of 3 commercial SARS-CoV-2 real time RT-PCR detection kits on nasopharyngeal swab samples, using the majority criterion. One hundred RNA samples informed as detectable (n=50) and not detectable (n=50) with GeneFinder-COVID-19 Plus RealAmp were selected, and later analyzed with BGI-Real-Time Fluorescent for Detecting SARS-CoV-2 and DisCoVery-SARS-CoV-2 RT-PCR. Agreement between tests was almost perfect; sensitivity was 100% for Genefinder and DisCoVery and less than 90% for BGI. Real time PCR products from 10 discordant samples were further analyzed by agarose gel electrophoresis, confirming 3 false negatives by BGI and suggesting 5 samples as true positives by DisCoVery. The use of DisCoVery and GeneFinder™ appear as an excellent choice with good sensitivity and specificity values.